Effects of Training in the Use of Argumentative Structures on ESL Students’ Argumentative Writing Ability - Zainuddin, Siti Zaidah (2006)
This study mainly investigated the effectiveness of training in the structure of arguments based on Toulmin’s (1958) model of argument on ESL students’ argumentative writing. In addition, this study was carried out to find out the contributing factors on the students’ poor performance in writing arguments. Twenty-one Form Five students were selected based on their Form Four English Language result. The instruments used were pretest composition questions, posttest composition questions, and in-depth interviews. The data and results collected were analyzed using the SPSS for the percentage, mean, standard deviation and t-tests. The experimental group showed a significant difference in the mean scores for each element of arguments after the treatment suggesting that the students demonstrated greater knowledge of argument criteria. The findings also exhibited significant pre- to posttest gains based on the Holistic Critical Thinking Rubric and SPM Marking Band. Besides that, the subjects showed positive response to the use of argumentative structure. The results of the interviews with the teachers proved that teachers seldom teach argumentative writing in class and prefer students to choose either narrative or descriptive essays. The interviews also suggested that there were no specific methods in their argumentative writing class. The results of the brainstorming session concluded that the Toulmin model helped them in developing and organizing their writing. When interviewed, they agreed knowing the structure of arguments helped them in writing argumentative essays better. Thus, these results proved that knowledge of argumentative structure sharpens students’ judgment regarding the content and organization of writing argumentative essays.